Factors Influencing Mobile Banking Adoption by Gen Z Generation - Riyawan Saputra (Penerbit Jurnal Indonesia, 2024)
This study aims to identify the factors influencing the adoption of mobile banking among Generation Z, known as digital natives with a lifestyle highly integrated with technology. Using a qualitative approach,The findings reveal several key factors affecting mobile banking adoption: ease of use, security and privacy, social influence, value-added services, technological accessibility, cost and efficiency, and alignment with digital lifestyles. Generation Z tends to prefer applications with simple interfaces, reliable security features, promotional incentives, and services tailored to their needs. Additionally, peer influence and recommendations from online communities play a significant role in their decision-making process. This study provides valuable insights for financial service providers to develop more effective strategies for increasing mobile banking adoption among this generation.